Right hemisphere stroke is linked to reduced social connectedness in the UK Biobank cohort - Katherine O’Connell; Abigail A. Marsh; Anna Seydell-Greenwald (Scientific Reports)
Abstract Social connectedness is fundamental to health and life satisfaction. Empathic capacities that support social connections are commonly impaired following damage to the brain’s right hemisphere, but how these acquired socio-emotional deficits correspond to real-world social outcomes remains unclear. Using anatomical brain imaging and behavioral data from a large sample of stroke survivors included in the UK Biobank (n = 209), we link damage to regions of the right hemisphere involved in emotion recognition to lower social relationship satisfaction and higher loneliness. The effect was driven by lesions to the right anterior insula and not explained by stroke extent and motor function; it was further corroborated by an exploratory analysis of social decline in a few participants for whom data were available from before and after a stroke to the right anterior insula (n = 3; comparison n = 13). These correlational findings provide new insight into the role of the right hemisphere in maintaining social connections and bear important implications for treatment and rehabilitation post-stroke.